Capitalism and the 'Animated Image': Politics of Morphing on the 'Culture' of Animation. (January 2014) - Ray, Kaustubh
The early animated image under industrial production was intrinsically antirealist in nature and was informed by the dialectics of class conflict. It was the result of the exploited labouring body working alongside the repressed erotogenic body within the industrial process of cinema animation. This was done under the logic of just exchange and wage labour. The dialectics of class conflicts manifests in early animation as the dialectics of morphing in the freedom of creative expression of the subject. Morphing not only talks of ideological freedom but also acts as the harbinger of counter-ideologies by destabilizing the animated image, literally and figuratively; thus creating the revolting animator and the curious spectator. Hence, the morph becomes a threat to property structure, acts beyond the logic of private interest of capital, resulting in the creation of the uncanny. Nevertheless, capital preempts morphing in animation by bringing it within the logic of capital, by rationalizing it. Capital in the form of technological advancements, being unable to push further into the classical two-dimensional process, took a leap towards the digital processes that changed the relations of production. This alienation was made absolute as the virtual space literally removed the animator from the tactile processes of hand drawn or stop motion techniques. The digital process came to the rescue of capital by gradually removing morphs from the animated image thereby altering the culture of animation in cinema.